A case of developmental pedophilia unmasked by frontotemporal dementia. Issue 2 (4th March 2021) - Prado, Catarina Sodré de Castro; Lopes, Pedro Maranhão Gomes; Moll, Jorge; DeSalles, Antonio; de Oliveira-Souza, Ricardo
ABSTRACT: A 65-year-old right-handed man gradually became socially indifferent and less active. Four years later, he was indicted for molesting children on multiple occasions. Psychomotor slowness and executive impairment contrasted with sparing of language, semantic memory, visuospatial perception, construction praxis, and right-left orientation. Neuroimaging showed asymmetric atrophy of dorsomedial frontal and anterior temporal lobes, and hypoperfusion of medial prefrontal cortex consistent with a diagnosis of behavioral variant of frontotemporal dementia. Further information revealed that the patient exhibited pedophilic behavior several years prior to symptom onset. We conclude that preexisting developmental pedophilia was "unmasked" by the underlying progressive frontotemporal degeneration.